DETERMINASI STATISTIK DAN IDENTIFIKASI PENYEBAB DOWNTIME MESIN PENGOLAH GARAM MENGGUNAKAN METODE FMEA UNTUK MENINGKATKAN PROSES PRODUKSI DI PT. XYZ - Aido Dongan, (2023)
PT XYZ is a manufacturing company engaged in food & beverage. PT XYZ is a company that produces iodized salt with the type of consumption salt and industrial salt. The object of the problem in this study is the downtime that occurred in the unit 5 production line of PT XYZ in 2022. This study aims to identify the causes of downtime, measure the frequency of downtime, and measure the probability of changes in output if there is an increase in the production process. From the stem and leaf plot method, and FMEA (Failure Mode Effect Analysis), the selected downtime was obtained, namely bucket trouble: loose bucket chain, slurry pump trouble: slurry pump, and Separator trouble: Separator motor burned out. In monte carlo simulation, simulations were carried out on the downtime frequency to reduce downtime (50%, 75%, 100%). In the Bayesian theorem, probability calculations were performed on each failure mode with four events. Of the 12 probabilities, the probability of failure mode resolved then downtime resolved in bucket trouble: loose bucket chain has the highest probability of 2.518.